Android mobile malware detection system using fuzzy AHP - Juliza, Mohamad Arif; Mohd Faizal, Ab Razak; Sharfah Ratibah, Tuan Mat (2021)
This research proposed a multi-criteria decision making based (MCDM) mobile malware detection system using a risk-based fuzzy analytical hierarchy process (AHP) approach to evaluate the Android mobile application. This study focuses on static analysis, that uses permission-based features to assess the mobile malware detection system approach.